Reklāmas loma produktu diferencēšanā - Kohena, Rebeka Elizabete (Latvijas Universitāte, 2023)
This paper examines the role of advertising in product differentiation. Some brands produce products that are practically identical or very similar to the products produced by the competition. It is known that advertising is a tool wielded by brands to set itself apart from others, but how is this tool wielded and is it needed to the same extent as it is used today? The author examined different classifications and types of advertisement as well as how did it work in the fast-food market. The research concentrated on the assessing the strength and direction of the relationship between advertising spending and revenues to figure out whether the advertising spending is justified or the brands can decrease advertising spending without hurting their revenues.
The Role of Advertising in Product Differentiation
Keywords: Ekonomika un uzņēmējdarbība; Advertising; Product Differentiation; Revenues; Advertising Expenses